Worshipping the Myths of World War II : Reflections on America's Dedication to War - Wood, Edward W., Jr (Book collections on Project MUSE., 2006)
Taking a critical look at America's dedication to war as panacea and as Washington's primary method for leading the world, this book reflects on such topics as the killing of innocents, how actual killing is usually ignored in war discussions and reporting, the lifetime impact of frontline duty, and more.